Communication pattern of Indonesian journalists with news source in the internet era - Wibawa, Darajat (Penerbit Universiti Kebangsaan Malaysia, 2018)
Indonesia is one of the countries that cannot evade the development of digital communication enabling its society to access the Internet. As such, now people can get Internet access easier, so that they can connect to it anytime and anywhere. This advantage, to some journalistic platforms like newspaper, radio, and television, is used to run an online version of their services as well as to search, collect, process and publish news for the society. Yet, the development of online journalism becomes a threat and challenge for newspaper, radio, and television journalism consecutively. All journalism media that exist previously compete each other to become the first and foremost in providing information to the society, thus the competition among journalists cannot be avoided, especially in searching information from news sources. In responding to this, even some journalists are willing to violate the rules in order to get a reliable news source. From this, it emerges a question what are the communication patterns applied between Indonesian journalists and the news sources seen from the eyes of the journalists? To answer this question, the researcher conducted the present study applying the qualitative approach. The results demonstrated that the patterns of communication done can be included into five categories such as mutualism, parasitism, commensalism, epigonism, and neutralism.